Genotyping and transmission analysis of Mycobacterium tuberculosis in a pediatric population in Czech Republic and Slovakia - Mäsiarová, Simona; Dvořáková, Věra; Hromádková, Michaela; Norman, Anders; Kunč, Peter; Fábry, Jaroslav; Hnilicová, Jarmila; Porvazník, Igor; Solovič, Ivan; Rasmussen, Erik M; Mokrý, Juraj; Doležalová, Karolína; et al. (BMC infectious diseases, 2025)
BACKGROUND: Tuberculosis remains a global health concern, with rising pediatric and adolescent cases. The advancement of diagnostic strategies is crucial for effective control, with whole-genome sequencing emerging as a promising tool. This study explores using whole-genome sequencing in pediatric Tuberculosis. METHODS: Mycobacterium tuberculosis isolates from pediatric patients and their contacts were collected between January 2023 and June 2024 in Slovakia and the Czech Republic. The isolates were subjected to WGS to characterize the resistance patterns and transmission. RESULTS: The study included 37 patients in total-30 pediatric cases and 7 adult index cases-with a single M. tuberculosis isolate collected per patient. The phylogenetic analysis results revealed that 32 out of 37 (86.5%) isolates belonged to the Euro-American lineage. Five isolates (13.5%) belonged to the East-Asian lineage. Genotypic resistance to at least one drug was confirmed in 6 patients (16%). 24 patients were divided into 9 clusters (65%), leaving 13 unclustered (35%). Moreover, the concordance between the identification of source case by WGS and epidemiological anamnesis was confirmed in 60% of patients. CONCLUSIONS: Epidemiological data may not always provide accurate insights into the transmission of TB. Consequently, integrating molecular methods, such as WGS, is essential to enhance the reliability and precision of epidemiological analyses.
Keywords: Infant; Humans; Phylogeny; Tuberculosis; kojenec; dítě; Drug resistance; Whole-genome sequencing; Child; Female; dospělí; Whole Genome Sequencing; Genotype; lidé; tuberkulóza; Slovakia; Slovenská republika; sekvenování celého genomu; předškolní dítě; Adult; ženské pohlaví; Male; fylogeneze; Mycobacterium tuberculosis; Adolescent; Transmission chains; Czech Republic; genotyp; Česká republika; mužské pohlaví; Child, Preschool; Pediatric patients, tuberculosis; mladiství